2020
DOI: 10.1002/acr.24055
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Arterial Disease in Takayasu Arteritis and Giant Cell Arteritis

Abstract: Objective. To identify and validate, using computer-driven methods, patterns of arterial disease in Takayasu arteritis (TAK) and giant cell arteritis (GCA). Methods. Patients with TAK or GCA were studied from the Diagnostic and Classification Criteria for Vasculitis (DCVAS) cohort and a combined North American cohort. Case inclusion required evidence of large-vessel involvement, defined as stenosis, occlusion, or aneurysm by angiography/ultrasonography, or increased 18 F-fluorodeoxyglucose (FDG) uptake by posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 31 publications
2
47
0
5
Order By: Relevance
“…The importance of FDG PET/CTA for the diagnosis of Takayasu arteritis has been proven in several newly published studies [30][31][32][33][34], but rare for childhood-onset disease [5,[18][19][20] (Table 1). FDG PET/CTA might be particularly valuable in patients with unspecific symptoms to detect alternative causes of systemic vasculopathy [16].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of FDG PET/CTA for the diagnosis of Takayasu arteritis has been proven in several newly published studies [30][31][32][33][34], but rare for childhood-onset disease [5,[18][19][20] (Table 1). FDG PET/CTA might be particularly valuable in patients with unspecific symptoms to detect alternative causes of systemic vasculopathy [16].…”
Section: Discussionmentioning
confidence: 99%
“…More vascular inflammation was observed in patients with GCA compared with TAK which could be due to biological differences, shorter disease duration in the patients with GCA, or differences in concomitant atherosclerosis. A large, international study also reported more FDG-PET activity in GCA and more angiographic damage in TAK in data collected at the time of diagnosis 36. Symptoms were defined as present or absent on the day of assessment, but the duration of those symptoms was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular lesions of TAK resemble those encountered in GCA and are composed of highly activated T cells and macrophages, arranged in granulomatous formations (6). In the past decade, TAK and GCA have often been considered to represent a spectrum of one disease, supported by similarities in target blood vessel patterning and histopathologic findings (9)(10)(11)(12). However, genome-wide associated studies and immunophenotyping of immune cells in the peripheral blood and in the vascular lesions have revealed substantial differences (18)(19)(20)57).…”
Section: Takayasu's Arteritismentioning
confidence: 99%
“…Damage patterns are similar in GCA and TAK, but the individuals at risk are clearly distinct based on geographic distribution and age at disease onset. Recent advances in non-invasive imaging techniques have demonstrated that the blood vessels targeted by GCA and TAK overlap, giving rise to the ongoing debate whether the two diseases are separate or within the same disease spectrum (9)(10)(11)(12). Molecular studies have emphasized that pathogenic events rely on cellular signal transduction pathways that are common in the two diseases, particularly when it comes to upstream pathologic effector functions of CD4 + T cells (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%